2008
DOI: 10.1677/joe-08-0319
|View full text |Cite
|
Sign up to set email alerts
|

Higher physical activity is associated with increased androgens, low interleukin 6 and less aortic calcification in peripheral obese elderly women

Abstract: The presence of peripheral fat mass (PFM) appears to counteract the atherogenic trends of central fat mass through mechanisms presently poorly understood. In elderly women with distinct forms of body fat distribution, we wanted to study whether physical activity and aortic calcification are related to plasma levels of cortisol, 17-a-hydroxyprogesterone (17-a-OHP), dehydroepiandrosterone (DHEA), androstenedione (ASD), and interleukin 6 (IL6) accomplishing an antiatherogenic milieu. A total of 276 well-defined g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
10
1
2
Order By: Relevance
“…In the recent Penn Ovarian Aging Study (13), no association between physical activity and DHEAS in any menopausal transition stage was found. The study of Straub et al (29), reported a positive association between physical activity and plasma levels of DHEAS in women with peripheral obesity. The results of this study should be interpreted with caution because these are not adjusted for potential confounders.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the recent Penn Ovarian Aging Study (13), no association between physical activity and DHEAS in any menopausal transition stage was found. The study of Straub et al (29), reported a positive association between physical activity and plasma levels of DHEAS in women with peripheral obesity. The results of this study should be interpreted with caution because these are not adjusted for potential confounders.…”
Section: Discussionmentioning
confidence: 96%
“…Only three other studies investigated the effect of physical activity on circulating levels of DHEAS in postmenopausal women, with mixed results (10,13,29). In a 12-month exercise trial among 170 postmenopausal women, McTiernan et al (11) did not observe any effect of the exercise intervention on DHEAS.…”
Section: Discussionmentioning
confidence: 99%
“…Among old women a linear association between CAC and PA could be demonstrated independent of multivariable adjustment [49]. Finally, Straub and coworkers [50] described in a cohort of 276 healthy women aged 60 - 85 years that PA was associated with an increase in the androgen to cortisol ratio as well low interleukin 6 and less severe abdominal aorta calcification postulating that the anti-atherogenic properties of PA may be mediated by the inhibition of inflammation operated by androgens [50]. …”
Section: Pa and Markers Of Subclinical Atherosclerosis In The Generalmentioning
confidence: 99%
“…Especula-se que a contração muscular induz a produção e liberação de IL-6 na circulação e contribui com a redução na produção de TNF-α (NICKLAS; BRINKLEY, 2009;STRAUB et al, 2008;FEBBRAIO;PEDERSEN, 2002 …”
Section: Síndrome De Fragilidade E Sarcopeniaunclassified
“…A imunossenescência compreende o fenômeno denominado inflammaging, que é uma regulação positiva da resposta inflamatória por modificação no perfil de citocinas pró-inflamatórias, e que vem sendo relacionado com doenças crônico-degenerativas e com o envelhecimento (GIUNTA, 2006 BRINKLEY, 2009;STRAUB et al, 2008), ou seja, quanto mais ativo fisicamente o indivíduo menor a chance dos efeitos indesejáveis de citocinas pró-inflamatórias. Sugere-se que ajustes adaptativos observados em fibras musculares e sistema imunitário inato ao exercício regular contribuem com a redução dos níveis basais de citocinas pró-inflamatórias, incluindo o TNF-α, IFN-γ e IL-1β (NICKLAS;BRINKLEY, 2009;PETERSEN;PEDERSEN, 2005).…”
Section: Efeitos De Prevenção E Terapêuticos Do Exercício Físicounclassified